Working time options over the life course: New Regulations and Empirical Findings in five European Countries - Christina Klenner; Yvonne Lott (Hans-Böckler-Stiftung, Wirtschafts- und Sozialwissenschaftliches Institut (WSI), 2016)
Employees in many European countries do have at their disposal various working-time options. Shorter working hours, leave options and flexible working-time arrangements enable employees to adjust their working time to meet their needs over the life course. The current study presents new national studies on working time options over the life course in five European countries. Laura den Dulk (the Netherlands), Dominique Anxo (Sweden), Sevil Sümer (Norway), Dorota Szelewa (Poland) and Hana Haésková and Renata Kyzlinková (the Czech Republic) report on the situation in their country. Christina Klenner and Yvonne Lott compare the results of the five studies and summarize the main findings.
urn:nbn:de:101:1-201612055391
Keywords: 330